Regulation of human trophoblast GLUT1 glucose transporter by insulin-like growth factor I (IGF-I). - Marc U Baumann; Henning Schneider; Antoine Malek; Vidya Palta; Daniel V Surbek; Ruth Sager; Stacy Zamudio; Nicholas P Illsley (PLoS ONE, 2014)
Glucose transport to the fetus across the placenta takes place via glucose transporters in the opposing faces of the barrier layer, the microvillous and basal membranes of the syncytiotrophoblast. While basal membrane content of the GLUT1 glucose transporter appears to be the rate-limiting step in transplacental transport, the factors regulating transporter expression and activity are largely unknown. In view of the many studies showing an association between IGF-I and fetal growth, we investigated the effects of IGF-I on placental glucose transport and GLUT1 transporter expression. Treatment of BeWo choriocarcinoma cells with IGF-I increased cellular GLUT1 protein. There was increased basolateral (but not microvillous) uptake of glucose and increased transepithelial transport of glucose across the BeWo monolayer. Primary syncytial cells treated with IGF-I also demonstrated an increase in GLUT1 protein. Term placental explants treated with IGF-I showed an increase in syncytial basal membrane GLUT1 but microvillous membrane GLUT1 was not affected. The placental dual perfusion model was used to assess the effects of fetally perfused IGF-I on transplacental glucose transport and syncytial GLUT1 content. In control perfusions there was a decrease in transplacental glucose transport over the course of the perfusion, whereas in tissues perfused with IGF-I through the fetal circulation there was no change. Syncytial basal membranes from IGF-I perfused tissues showed an increase in GLUT1 content. These results demonstrate that IGF-I, whether acting via microvillous or basal membrane receptors, increases the basal membrane content of GLUT1 and up-regulates basal membrane transport of glucose, leading to increased transepithelial glucose transport. These observations provide a partial explanation for the mechanism by which IGF-I controls nutrient supply in the regulation of fetal growth.